COVID-19 et assistance circulatoire - Hekimian, G. (Ann Cardiol Angeiol (Paris), 2020)
Extracorporeal membrane oxygenation (ECMO) is mainly used as a rescue therapy in COVID-19 patients with severe acute respiratory distress syndrome (ARDS). More rarely, COVID-19 can be complicated by hemodynamic failure due to fulminant myocarditis or massive pulmonary embolism necessitating the implantation of venous-arterial ECMO. The management of ECMO during the COVID-19 pandemic is challenging due to some specificities related to the disease characteristics, such as the management of anticoagulation in patients with a hypercoagulable state and an increased risk of venous thromboembolism. In large retrospective cohorts, survival of ECMO-rescued COVID-19 patients with ADRS was reported to be similar to that reported in previous studies on ECMO support for severe ARDS. Full consideration of ECMO candidacy is crucial for appropriate allocation of resources.